Facile room temperature synthesis of ZnO nanoflower thin films grown at a solid-liquid interface - Jadhav, Aarti H.; Patil, Sagar H.; Sathaye, Shivaram D.; Patil, Kashinath R. (Journal of Materials Science, 2014)
Hierarchical ZnO films consisting of nanoflower particulates are successfully grown by a solid-liquid interface reaction technique at room temperature without additives like surfactants, capping agent, or complexing agent. The structural, morphological, and photocatalytic properties of these films are studied using scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and UV-Vis spectroscopy. The nucleation, growth processes and hence the resulting morphology of the end product can be regulated by changing the concentration of LiOH and the time of reaction. SEM throws light on the chronology of the flower formation by studying the intermediate morphology. Electron microscopy results indicated that these ZnO nanostructures self-assembled to produce flower-like nanostructures. The highest photocatalytic efficiency was observed for the films prepared at the concentration of LiOH 0.5 mg/mL in ethanol at 24 h. On the basis of the results, a plausible growth mechanism for the formation of flower-like ZnO nanostructures is discussed.

Method to form semiconductor quantum dot (QD) thin films by igniting a flame at air-liquid interface: CdS and WO3 - Jadhav, Aarti H.; Patil, Sagar H.; Sathaye, Shivaram D.; Patil, Kashinath R. (Journal of Colloid and Interface Science, 2015)
We reveal an easy, inexpensive, efficient one step flame synthesis of semiconductor/metal oxide thin films at air-liquid interface, subsequently, transferred on suitable substrate. The method has been illustrated by the formation of CdS and Wo(3) QDs thin films. The features of the present method are (1) Growth of thin films consisting of 0.5-2.0 nm sized Quantum Dots (QDs)/(ultra-small nanoparticles) in a short time, at the air-liquid interface which can be suitably transferred by a well-known Blodgett technique to an appropriate substrate, (2) The method is suitable to apply layer by layer (LbL) technique to increase the film thickness as well as forming various compositions as revealed by AFM measurements. The films are characterized for their structure (SAED), morphology (TEM), optical properties (UV-Vis.) and photoluminescence (PL). Possible mechanism of formation of QDs thin film and effect of capping in case of COS QDs is discussed. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: CdS; Flame synthesis; interface; Quantum Dots (QDs); thin film; WO3